PROGRESSIVE ASSEMBLY TECHNOLOGY OF RADIAL ANGULAR-CONTACT BALL BEARINGS WITH INNER-COOLED RACE - Albert V. Korolev; Vladimir V. Bolkunov; Artem G. Miroshkin; Olga P. Reshetnikova (Advanced Engineering Research, 2012)
The experimental data in the field of the radial angular-contact ball bearings are resulted. The cold assembly technology for the radial angular-contact ball bearings, in which the inner race cooling temperature is determined with its aftercontraction to provide the ball bearing assembly support, is worked out.